Household food security is associated with growth of infants and young children in rural Bangladesh - Saha, Kuntal K.; Frongillo, Edward A.; Alam, Dewan S.; Arifeen, Shams E.; Persson, Lars; Rasmussen, Kathleen M. (Cambridge University Press, 2009)
Despite a strong relationship between household food security and the health and nutritional status of adults and older children, the association of household food security with the growth of infants and young children has not been adequately studied, particularly in developing countries. We examined the association between household food security and subsequent growth of infants and young children in rural Bangladesh.We followed 1343 children from birth to 24 months of age who were born in the Maternal and Infant Nutrition Intervention in Matlab (MINIMat) study in rural Bangladesh. A food security scale was created from data collected on household food security from the mothers during pregnancy. Data on weight and length were collected monthly in the first year and quarterly in the second year of life. Anthropometric indices were calculated relative to the 2006 WHO child growth standards. Growth trajectories were modelled using multilevel models for change controlling for possible confounders.Household food security was associated (P < 0·05) with greater subsequent weight and length gain in this cohort. Attained weight, length and anthropometric indices from birth to 24 months were higher (P < 0·001) among those who were in food-secure households. Proportions of underweight and stunting were significantly (P < 0·05) lower in food-secure households.These results suggest that household food security is a determinant of child growth in rural Bangladesh, and that it may be necessary to ensure food security of these poor rural households to prevent highly prevalent undernutrition in this population and in similar settings elsewhere in the world.